Strategy to Develop Rice Farm Business Insurance in PT Asuransi Jasa Indonesia - Graita Gaiety Jatmiko; Arief Daryanto; Rokhani Hasbullah (School of Business, IPB University (SB-IPB), 2017)
Agricultural sector has very significant roles in Indonesian economy, some of which are as the contributor of the second highest PDB and the biggest labor absorber with the contribution of 13.6% and 32% respectively. Even though, it is the biggest labor absorber,agricultural business is not interesting to the community nowadays. This is because this business has a quite high risk to fail to harvest. This research aimed to analyze the external and internal factors affecting the development of Rice Farm Business Insurance (AUTP), to know the position of the company in carrying out the AUTP, and to formulate the strategy to develop AUTP in PT Asuransi Jasa Indonesia (Jasindo). This research used descriptive method through case study with the analysis equipment, like Five Forces Porter, IFE/EFE Matrix, IE Matrix, SWOT, and QSPM. The results showed that there were several strategic factors influencing the implementation of AUTP, i.e. a wide market opportunity. The position of the company in the implementation of AUTP was in the position of hold and maintain with the recommended strategy, of market penetration and product development. In this research, eight alternative strategies were obtained with the with the highest priority was to expand the distribution channel network.Keywords: development stragety, rice farm business insurance,agricultural risk, Jasindo, QSPM